Availability and use of mHealth for disease diagnosis and treatment support by health workers in sub-Saharan Africa: a scoping review protocol - Tivani Phosa Mashamba-Thompson; Desmond Kuupiel; Ernest Osei (BMJ Open, 2020)
Introduction Improving healthcare for all is one of the global health priorities, particularly in disease burdened settings such as sub-Saharan Africa (SSA). Considering the high penetration rate of mobile phones in SSA, mobilehealth (mHealth) could be used to achieve universal health coverage. The proposed study will map evidence on the availability and use of mHealth for disease diagnosis and treatment support by health workers in SSA.Methods and analysis This review will be guided by Arksey and O'Malley’s scoping review framework and Levac et al’s recommendations and guidelines from the Joanna Briggs Institute. A scoping review will be conducted to explore what is known about mHealth for disease diagnosis and treatment support by health workers in SSA and to identify areas for future research. In addition to searching the grey literature, the following databases will be explored from PubMed, MEDLINE and CINAHL with full text via EBSCOhost and ScienceDirect databases. A search in Google Scholar will be considered as an additional information source. The literature search will involve published studies from 2000 to 2020 in any language. This review will cover mHealth for disease diagnosis and treatment support by health workers in SSA. The primary investigator will conduct the title screening, and subsequently, two reviewers will independently conduct abstract and full article screening and data extraction. The results of this proposed review will be presented using the Preferred Reporting Items for Systematic Reviews and Meta-analysis: Extension for Scoping Review guidelines.Ethics and dissemination Ethical approval is not required for the scoping review, which is the first stage in a PhD study in public health on accessing mHealth for disease diagnosis and treatment support by health workers in Ghana. The final review will be submitted for publications to a scientific journal, and our results will be presented at appropriate conferences.